Peran Financial Self-Efficacy Pada Kualitas Pembelajaran Akuntansi Dan Keuangan Terhadap Keputusan Investasi - Magdalena, Febriani Cristina Susianti; Rita Amelinda; Anwar, Roseline Mannuela; Oktavini, Eva (Jurnal Ekonomi, 2023)
This study examines two aspects, namely the impact of the quality of learning in Accounting and Finance on investment decisions; and the role of the financial self-efficacy aspect as an intervening variable that links the quality of Accounting and Finance learning to investment decisions. This study using primary data obtained through distributing questionnaires to 375 students of the Faculty of Economics and Business who had received education about finance, investment and capital markets, and had started investing. this research uses Structural Equation Modeling via Smart-PLS to carry out the analysis. The results obtained show that financial self-efficacy mediates the relationship between the quality of Accounting and Finance learning on investment decisions.